Emergent Properties of Natural Products - Herzon, Seth B. (Synlett, 2018)
Emergence is the phenomenon by which novel properties arise from the combination of simpler fragments that lack those properties at their given levels of hierarchal complexity. Emergence is a centuries-old concept that is commonly invoked in biological systems. However, the penetration of this idea into chemistry, and studies of natural products in particular, has been more limited. In this article I will describe how the perspective of emergence provided a framework to elucidate the complex properties of two classes of natural products – the diazofluorene antitumor agent lomaiviticin A and the genotoxic bacterial metabolites known as colibactins, and sets the stage for a third class of molecules – antibiotics derived from the fungal metabolite pleuromutilin. Embracing the idea of emergence helped us to connect the aggregate reactivities of the colibactins and lomaiviticin A with their biological phenotypes. Emergence is a top-down approach to natural products and complements the classical bottom-up analysis of functional group structure and reactivity. It is a useful intellectual framework to study the complex evolved properties of natural products.1 Introduction2 Diazofluorenes3 Precolibactins and Colibactins4 Pleuromutilins5 Discussion and Conclusion
Keywords: emergence; natural products; lomaiviticin; colibactins; functional group reactivity